Digital Dopamine: Pengertian, Dampak dan Langkah Mengatasinya - Akhmad Syah Roni Amanullah; Arbin Janu Setiyowati; Jamiatul Hasanah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
he phenomenon of digital dopamine refers to the release of the neurotransmitter dopamine in the brain in response to instant digital stimulation from devices, social media, and online games. This article aims to comprehensively examine the concept of digital dopamine, its impact on children's behavior and psychological functions, as well as practical measures to address it within family and school contexts. The method employed is a literature study with a descriptive qualitative approach, analyzing 25 primary sources consisting of psychology journals, neuroscience journals, guidance and counseling journals, and reports from international organizations published between 2019 and 2026. The findings indicate that digital dopamine contributes to decreased focus capacity, increased impulsivity, impaired emotional regulation, and a tendency toward addictive device use. Mitigation strategies include gradual digital detoxification, activity substitution, implementation of device-free zones, and strengthening the roles of parents and school counselors. This article affirms that digital dopamine is not merely a metaphor but a neurobiological phenomenon that necessitates a systematic approach based on family dynamics and guidance and counseling services in school.